2001
DOI: 10.1007/s003830000455
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic dilemmas in abdominal tuberculosis in children

Abstract: The authors review 45 pediatric patients with intra-abdominal tuberculosis (ATB) treated between May 1990 and April 1998. The diagnosis was confirmed histologically or by positive culture for Mycobacterium tuberculosis. Clinical presentation was with an abdominal mass (12), subacute obstruction (11), ascites (5), mass and ascites (4), peritonitis (4), and 9 unusual presentations. Mantoux tests were positive in 68% of patients tested. There were radiologic features suggestive of pulmonary TB in 29 patients (64%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 0 publications
2
21
1
3
Order By: Relevance
“…One patient (patient 1) presented with small-bowel obstruction due to chronic peritoneal inflammation and adhesions. Intestinal obstruction developed in patients with TBP is also reported in the other studies [4,[11][12][13] . Due to the nonspecific symptoms and physical findings, diagnosis is often delayed.…”
Section: Discussionsupporting
confidence: 77%
“…One patient (patient 1) presented with small-bowel obstruction due to chronic peritoneal inflammation and adhesions. Intestinal obstruction developed in patients with TBP is also reported in the other studies [4,[11][12][13] . Due to the nonspecific symptoms and physical findings, diagnosis is often delayed.…”
Section: Discussionsupporting
confidence: 77%
“…Differentiating between GIT TB and Crohn's disease is important in countries with a low incidence of TB as immigration and travel are increasing and immunosuppressant agents are often used in the treatment of Crohn's disease 34 . M. tuberculosis is grown from an abdominal specimen in only 36–40% of cases and may take 6–8 weeks 30 33. Ziehl–Neelsen staining is positive in only 32–35% and lacks specificity 21 27 30.…”
Section: Discussionmentioning
confidence: 99%
“…Chest radiographs were reported to be abnormal in 50% to 75% of abdominal TB patients (3,10,31). In the present study, the chest radiographs of seven patients (one had no chest radiograph) clearly indicated lung involvement of TB.…”
Section: Discussionsupporting
confidence: 44%